Development of Digital Biology Book on Antioxidant Activity of Red Dragon Fruit Extract (Hylocereus polyrhizus) for Class XI High School Students - Sindy Sataroh; Novi Febrianti (Journal of Education and Learning Research, 2024)
With technological advances, digital-based learning resources are needed that can be studied by students independently. The results of the research can be used as a learning resource, one of which is in the form of a digital book. This study aims to determine the quality and feasibility of digital books compiled as learning resources. The type of research is research and development (R&D) which refers to the 4D development model (Define, Design, Development and Disseminate). Data collection techniques with instruments in the form of expert assessment questionnaires and response questionnaires. The research subjects consisted of material experts, media experts, biology teachers and 37 students of SMA N 1 Koba class XI. Product data were analyzed descriptively qualitatively to determine the quality and feasibility of the compiled digital book. The results of research and development (R&D) obtained a Digital Book product for high school students class XI bioprocess material. Product assessment by material experts 88.64% (very good), media experts 86.11% (very good), biology teacher experts 100% (very good). The results of the small-scale test of students were 94.29% (very good) and the large-scale test was 98% (very good). Results Based on this research, digital books are appropriate to be used as a learning resource for class XI cell bioprocess materials.